Sustainable solutions for workable and strong concrete: cordia gel and waste engine oil admixtures - Danish Kumar,; Fareed Ahmed Memon,; Fahad ul Rehman Abro,; Satram Das, (Penerbit Universiti Kebangsaan Malaysia, 2024)
To produce high strength or rich cement concrete having low water to cement ratio with adequate workability is the biggest challenge for the construction industry. To achieve the necessary workability, the world is now using costly chemical admixtures. Research should be carried out to explore materials having potential to be utilized as cost-effective chemical admixtures in concrete. The primary goal of this research is to investigate the combined effect of Cordia Gel (CG) and Waste Engine Oil (WEO) as chemical admixtures on fresh and hardened properties of concrete. Fresh properties of concrete were examined in terms of workability and hardened properties were investigated by compressive strength test and Ultrasonic Pulse Velocity (UPV) test on cubical specimen of dimensions 100mm x 100mm x 100mm after 7, 28 and 90 days of curing in water. Four different percentages of WEO (0.5%, 1%, 1.5% and 2%) were used and percentage of CG kept constant as 0.5% with respect to weight of cement and results were compared with the control mix. Results revealed that workability of fresh concrete increased with increasing amount of CG and WEO. However, a decreasing trend was observed for compressive strength and UPV of hardened concrete when higher values of admixtures were added. The usage of CG and WEO as chemical admixtures in concrete can be a sustainable and cost-effective way to achieve the desired results.